Plasma Nitriding of Bored Barrels (Advances in Military Technology, 2022)
The nitriding behaviour of heat-treated alloyed steel was carried out on two samples with various diameters. The influence of nitriding conditions on the thickness and hardness of nitrided layer were investigated. Bored cylindrical barrels were quenched and subsequently tempered. Plasma nitriding was performed at 500°C for 6 hours with mixture of H2 and N2 in plasma nitriding appliance. The pressure was changed to 4 and 6 mbar. Microstructure and mechanical properties of nitrided layers were characterized using optical spectrometry, laser microscopy, hardness testing. The nitrided depth was also estimated using cross-sectional microhardness profiles. The results of experiments showed that plasma nitriding process is applicable to cavities. Surface hardness of material was significantly increased. The measurements have shown that the pressure of plasma nitriding process has a remarkable influence on the depth of nitriding in cavities, flat surfaces and on the length of nitriding inside cavities, i.e. the distance from muzzle.
Keywords: plasma nitriding; nitrided layer; universal hardness; length of nitriding